2017
DOI: 10.1007/978-3-319-47754-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review of (Q)SAR Modelling of Nanomaterial Toxicity

Abstract: Despite the clear benefits that nanotechnology can bring to various sectors of industry, there are serious concerns about the potential health risks associated with engineered nanomaterials (ENMs), intensified by the limited understanding of what makes ENMs toxic and how to make them safe. As the use of ENMs for commercial purposes and the number of workers/end-users being exposed to these materials on a daily basis increases, the need for assessing the potential adverse effects of multifarious ENMs in a time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 119 publications
0
10
0
Order By: Relevance
“…Previous reports indicated that the typical nanoplastic concentrations were 150–2400 particles/m 3 , whereas in a harbor adjacent to a plastic production facility, the concentration was 102,000/m 3 . 44 We have tested the toxicological effects of nanoplastics using a median lethal concentration (LC 50 ) assay, 45 followed by for a series of concentrations lower than LC 50 for subsequent experiments. However, for investigating the toxic effects and mechanisms of nanoplastics on aquatic organisms, the complicated environmental factors might disturb the effects of nanoplastics in organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that the typical nanoplastic concentrations were 150–2400 particles/m 3 , whereas in a harbor adjacent to a plastic production facility, the concentration was 102,000/m 3 . 44 We have tested the toxicological effects of nanoplastics using a median lethal concentration (LC 50 ) assay, 45 followed by for a series of concentrations lower than LC 50 for subsequent experiments. However, for investigating the toxic effects and mechanisms of nanoplastics on aquatic organisms, the complicated environmental factors might disturb the effects of nanoplastics in organisms.…”
Section: Discussionmentioning
confidence: 99%
“…key descriptors) bridging to nanomaterial properties and the observed effects. Oksel et al (2017) proposed three criteria on datasets for modeling: data should be obtained from a preferably single and standardized protocol; its accuracy and suitability for (Q)SAR analysis should be examined; and datasets should be large enough to allow rational division of the data into training and test sets (Oksel et al 2017). Here we have used a unique dataset that fulfills these criteria, in that it comprises a very well characterized panel of nanomaterials that has been evaluated in different assays, both, in vitro and Table 10.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of workers or end users who use them for commercial purposes and are exposed to these chemicals every day increases, the need to assess their potential side effects in a cost-effective manner is growing. These data-driven models can be used to accelerate the decision-making process by screening hazards, and making early identification and management of potential toxicity, and physicochemical properties; and maximizing the use of information that these models provide can also support the industrial, regulatory, and public needs for safer chemicals [64]. In addition, further research is needed on how to use the in silico programs to protect workers' health in industries that manufacture, use, and distribute various chemicals.…”
Section: Resultsmentioning
confidence: 99%